Performance of the Bangladesh economy : selected issues - Rahman, Rushidan Islam; Bangladesh Institute of Development Studies (Dhaka : Bangladesh Institute of Development Studies, 2003)
Contributed papers presented at a seminar held in April 2002.
Performance of the Bangladesh economy : selected issues, introduction and overview / Rushidan Islam Rahman -- Bangladesh, external sector peformance and recent issues / Mustafa K. Mujeri -- Pattern and sustainability of economic growth in Bangladesh / Rushidan Islam Rahman -- Crop and horticulture production in Bangladesh : performance and prospects / Quazi Shahabuddin -- Performance and prospects of livestock production in Bangladesh / Md. Abdul Quasem -- Role of the export processing zones in the industrialisation process of Bangladesh : lessons for the future / Abdul Hye Mondal -- Enabling women to contribute to economic growth : an analysis of allocations in the national budget of Bangladesh / Pratima Paul-Majumder, Atiur Rahman, Zulfiqar Ali -- To school or not : determinants of school enrolment in Bangladesh / M. Asaduzzaman.
Includes bibliographical references.
Keywords: Bangladesh -- Economic policy -- Congresses; Bangladesh -- Economic conditions -- Congresses